Entre a medicina e a branquitude : as políticas de ações afirmativas em um ambiente de formação médica em Belo Horizonte - Tiago Heliodoro Nascimento (2022)
This thesis seeks to study the relationship between medicine and whiteness in Brazil, and to observe how affirmative action policies for black people in federal public universities have displaced this relationship. After presenting and exploring my place as a black man formed by the first quota policies in Brazilian universities in the early 2000s, as well as my experiences as a militant for the implementation of affirmative action in my own postgraduate course in anthropology, and showing how these experiences conducted a research on its effects on the medical course, initially, the research seeks to identify the historical relationships between medicine and whiteness in Brazil. In this sense, it performs a critical bibliographic review of works by historians of medicine, mainly observing how characters and institutions of Brazilian medicine are represented. Bearing in mind that they are almost all white, pay attention to the discursive strategies that disassociate whiteness and medicine from any negative perception. The parallelism and overlapping of processes stand out, such as the institutionalization of medicine (creation of schools, representative bodies and their approximation with the state), the struggles of African and Brazilian black people against enslavement, and the accommodation of theory eugenics in Brazil. By intertwining these movements, it identifies how medicine operated in the updating of racist terms and practices, and argues that, more than negative representations around the black experience, medicine was an agent of defense of white racial superiority. In this way, he defends the importance of talking about white supremacy in Brazil. Through an ethnographic effort, the thesis looks at materialities of the Memory Center of the Faculty of Medicine of UFMG to identify it as more than an organizer of medical memories, but as a center of white memorabilia. Theoretically, the thesis is based mainly on the concept of raciality/biopower apparatus, developed by Sueli Carneiro (2005), an idea that seeks to understand and relate to references from whiteness critical studies, especially Maria Aparecida Silva Bento (2002) and her concept of the narcissistic pact of whiteness, both fundamental tools both in historiographical criticism and in the approach of interviews and field experiences that I had with students and professors of medical courses in Belo Horizonte. From then on, it goes through questions raised by the field, such as those around the racial profile of corpses historically used for anatomy classes in medicine courses in Brazil, bodies of black and poor people, and explores the potential of this information for the representation of the of raciality/biopower apparatus (Carneiro, 2005). In the approach of the interviews, it highlights how the medical course is composed of a fraction of the whiteness class that lives in a condition of racial confinement, and analyzes how racial quotas have impacted the racial self-recognition of white people, in particular, it seeks to show how the potency of the ideology of miscegenation in Brazilian culture justifies the importance of racial heteroidentification committee in the implementation of affirmative action policies for black people and how they contribute to the defense of the idea of racial self-declaration. An anti-racist right that protects Negritude, that is, the recovery, on the part of those who were redefined as blacks during colonization, of the condition of saying what they are, who they were, and what they want to be.